There is no Ethan : how three women caught America's biggest catfish - Akbari, Anna (Grand Central, 2024)
"There is no Ethan" catalogues Akbari's experiences as both victim and investigator of a catfishing scheme to emotionally con women. She joins with two other women to track down the perpetrator and explores what it means to live in a world where technology mediates relationships and truth, reality, and identity have become slippery terms.